Prevalence of disordered eating, Eating disorders and risk of low energy availability in professional, competitive and recreational female athletes based in the United Kingdom - Sharps, F. R. J.; Wilson, L. J.; Graham, C. A.-M.; Curtis, C. (European Journal of Sport Science, 2022)
Eating disorders (ED), disordered eating (DE) and low energy availability (LEA) can be detrimental to health and performance. Previous studies have independently investigated prevalence of ED, DE or LEA, however few combined methods have identified risk within female athletes. The aim of this study was to identify prevalence of ED, DE and LEA in UK-based female athletes and investigate whether associations exist between age, competition level and primary sport. The Female Athlete Screening Tool (FAST) and Low Energy Availability in Females Questionnaire (LEAF-Q) were used in a cross-sectional study design. A total of 112 responses eligible for analysis were received. A total of 16%, 44% and 53% of female athletes were at risk from ED (FAST: >94), DE and LEA, respectively. Competition level (recreational, competitive or professional athletes; Fishers, p=0.05), influenced, and was a predictor of FAST (R2 = 0.076, F(1,110) = 10.067, p=0.05, variance inflation value; VIF = 1.0) whereas age influenced (Age: H(2) = 13.128, p=0.05), and was a predictor (R2 = 0.144, F(2,109) = 9.170, p =0.05, VIF = 1.0) of LEAF-Q. A positive correlation was observed between FAST and LEAF-Q scores (R = 0.496, p=0.05). Age and competition level may be predicting risk factors of ED/DE and LEA within female athletes, however further research is required to support the findings of this present study.